2021
DOI: 10.3390/pr9111873
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Platinum Based Cytostatic Drugs: From Detection to Removal

Abstract: The uncontrolled release of pharmaceutical drugs into the environment raised serious concerns in the last decades as they can potentially exert adverse effects on living organisms even at the low concentrations at which they are typically found. Among them, platinum based cytostatic drugs (Pt CDs) are among the most used drugs in cancer treatments which are administered via intravenous infusion and released partially intact or as transformation products. In this review, the studies on environmental occurrence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 155 publications
0
8
0
Order By: Relevance
“…Cisplatin and cyclophosphamide are two alkyl agents which are widely used to treat cancer patients [29,30]. Like most chemotherapeutic agents with anti-neoplastic actions, there are known to have numerous adverse effects including but not limited to nausea, alopecia, or cognitive impairments [31][32][33][34][35]. Throughout the study, no mice were found dead or had to be terminated due to health conditions, confirming the relevance of the dose selection.…”
Section: Clinical Evaluation Of Body Weight Change Revealed Mild Alte...mentioning
confidence: 66%
“…Cisplatin and cyclophosphamide are two alkyl agents which are widely used to treat cancer patients [29,30]. Like most chemotherapeutic agents with anti-neoplastic actions, there are known to have numerous adverse effects including but not limited to nausea, alopecia, or cognitive impairments [31][32][33][34][35]. Throughout the study, no mice were found dead or had to be terminated due to health conditions, confirming the relevance of the dose selection.…”
Section: Clinical Evaluation Of Body Weight Change Revealed Mild Alte...mentioning
confidence: 66%
“…The stability of carboplatin in aqueous solution is more closely related to nucleophiles concentrations and the pH of the medium, and, in all cases, this activation process is slower than that of cisplatin. Oxaliplatin produces reactive species that contaminate groundwater depending on the composition of the aqueous solution [ 94 ].…”
Section: Stability Of Anticancer Drugsmentioning
confidence: 99%
“…The detection frequency of anticancer drugs in hospital wastewater is 58% and cisplatin is marked as one of the most hazardous pharmaceuticals (Dan et al, 2021). The presence of cisplatin in waterbodies even at ng/l concentrations can cause toxic effects on aquatic species (Roque-Diaz et al, 2021) The surface water Watch List (WL) includes information about emerging pollutants that can cause a significant risk to aquatic organisms and humans upon consumption of contaminated drinking water. This list contains all the above-mentioned groups of pharmaceuticals (Gomez Cortes et al, 2022).…”
Section: Effect Of Pharmaceuticals On the Environment And Human Healthmentioning
confidence: 99%